An effective Pd nanocatalyst in aqueous media: stilbene synthesis by Mizoroki–Heck coupling reaction under microwave irradiation - Garcia, Carolina Soledad (2017)
Aqueous Mizoroki–Heck coupling reactions under microwave irradiation (MW) were carried out with a colloidal Pd nanocatalyst stabilized with poly(N-vinylpyrrolidone) (PVP). Many stilbenes and novel heterostilbenes were achieved in good to excellent yields starting from aryl bromides and different olefins. The reaction was carried out in a short reaction time and with low catalyst loading, leading to high turnover frequency (TOFs of the order of 100 h−1). The advantages like operational simplicity, high robustness, efficiency and turnover frequency, the utilization of aqueous media and simple product work-up make this protocol a great option for stilbene syntheses by Mizoroki–Heck reaction.